2015
DOI: 10.1097/md.0000000000000659
|View full text |Cite
|
Sign up to set email alerts
|

Serum Golgi Protein 73 (GP73) is a Diagnostic and Prognostic Marker of Chronic HBV Liver Disease

Abstract: Alanine aminotransferase (ALT) is the most commonly used marker of liver injury, but normal ALT levels are seen in a proportion of chronic hepatitis B virus (HBV)-infected patients with severe liver injury. Golgi protein 73 (GP73) is a promising alternative marker of liver injury. This study assessed the relation between GP73 levels and liver disease severity, monitored the kinetic changes in GP73 levels in chronic HBV patients receiving entecavir (ETV) therapy, and investigated the potential diagnostic and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
48
0
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 32 publications
6
48
0
2
Order By: Relevance
“…Recently, an established hepatocellular carcinoma (HCC) biomarker, serum Golgi protein 73 (GP73), was reported to be correlated with disease severity in chronic hepatitis B (CHB) . The increased serum GP73 in HCC is argued to be attributed to the presence of cirrhosis rather than HCC .…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Recently, an established hepatocellular carcinoma (HCC) biomarker, serum Golgi protein 73 (GP73), was reported to be correlated with disease severity in chronic hepatitis B (CHB) . The increased serum GP73 in HCC is argued to be attributed to the presence of cirrhosis rather than HCC .…”
Section: Introductionsupporting
confidence: 63%
“…The second strength was the usage of liver biopsy as gold standard for fibrosis staging . Previous reports were limited by small sample sizes and lack of liver biopsy as reference method . Thus, our data provided the strongest evidence to date.…”
Section: Discussionmentioning
confidence: 78%
“…A similar magnitude of increased GP73 expression was observed in fully established cirrhosis. Consistently, a recent study demonstrated that the levels of sGP73 were low in chronic HBV carriers without liver injury, but they were significantly elevated in patients with prominent hepatic injury and fibrosis, and the sGP73 levels were positively correlated with the severity of liver injury, indicating that the affected hepatocytes released more GP73 into the blood when liver injury was triggered (27). Therefore, the increase of sGP73 is a common feature of liver injury, regardless of the causes.…”
Section: Discussionsupporting
confidence: 60%
“…Non-invasive predictive models of fibrosis are therefore needed. Single markers have been proposed such as platelet count, AST and ALT, gamma-globulins, serum HBsAg levels, CP, red blood cell distribution width, Interleukin-2R, TGF-α, serum Golgi protein 73 (GP73), and miR-122[13,14,16,17,25,28-31]. However, currently, none of these markers are sufficiently liver-specific enough to accurately reflect fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Serum markers of liver fibrosis and non-invasive predictive models of fibrosis can evaluate fibrosis specifically in HBV patients due to high applicability, inter-laboratory reproducibility, wide availability for repeated assays, and limited cost[13-18]. However, in CHB patients with ALT < 2 × ULN, few non-invasive approaches have been developed to evaluate liver fibrosis[14,19-21].…”
Section: Introductionmentioning
confidence: 99%